2011
DOI: 10.1016/j.procs.2010.12.061
|View full text |Cite
|
Sign up to set email alerts
|

The impact of information technology on E. marketing

Abstract: Information technology has been considered the greatest innovation of the new era because it has a lot of fruitful social economic and scientific impacts. Regarding the economic effect, information technology has been of the essence into bringing the E. marketing into existence. The main purpose of this study is to investigate the effect of information technology in E. marketing. The data are gathered in different ways: from the balance sheet and income statement of the companies; from government agencies; fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Internet juga telah menjadi bagian faktor penting dari kehidupan sehari-hari. Buku, ensiklopedia, dan bahkan dalam beberapa kasus surat kabar telah berangsur-angsur digantikan oleh internet [1]. Kemajuan teknologi, komputer, dan telekomunikasi telah memberikan dukungan bagi perkembangan teknologi internet.…”
Section: Pendahuluanunclassified
“…Internet juga telah menjadi bagian faktor penting dari kehidupan sehari-hari. Buku, ensiklopedia, dan bahkan dalam beberapa kasus surat kabar telah berangsur-angsur digantikan oleh internet [1]. Kemajuan teknologi, komputer, dan telekomunikasi telah memberikan dukungan bagi perkembangan teknologi internet.…”
Section: Pendahuluanunclassified
“…Likewise, Trivedi (2013) reiterates the fact that the organizations evolve in the knowledge process of consumers through innovating practices, mostly in marketing, emphasizing the use of Internet (digital marketing), which will produce more adequate strategies to the current market. Trainor, Rapp, Beitelspacher, & Schillewaert (2011) establish that the incorporation of innovation through new technologies is a key component in order to create digital marketing inside enterprises that would provide a better interaction with clients and give a better and higher access to information (El-Gohoray, 2010), at the same time that the enterprise would show an image of quality (Hamidi & Safabakhsh, 2011), by taking advantage of the new technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the presence of globalisation facilitates technological improvements which enable things to be easily accessed to produce HBEs that can reach international markets (Tyas et al, 2021). Researchers observed that Internet users can help HBEs provide opportunities; improve marketing and operational efficiency with lowered costs for business enterprise (Hamidi & Safabakhsh, 2011;Eid & El-Kassrawy, 2012;Hanafizadeh et al, 2012;Eid & El-Gohary, 2013;Tyas et al, 2021). With the use of internet trading, positive opportunities are created for HBEs in ways that were formerly impossible promoting business-to-consumer competitive advantage, and business-to-business costbenefit (Leeflang et al, 2014;Tyas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%